AB0611 Hypovitaminosis d and osteopenia/osteoporosis in a haemophilia population. (23rd January 2014) - Melchiorre, D.; Linari, S.; Montorzi, G.; Bartolozzi, D.; Borderi, M.; Benelli, M.; Morfini, M.; Matucci-Cerinic, M.
Abstract : Background: Recent reports show a correlation between haemophilia and bone mineral density reduction. HIV, HCV and their treatments are independently associated to an increased risk of osteoporosis. A pivotal role in bone mineralization is played by Vitamin D. Objectives: This study compares Vitamin D level, bone metabolism markers and bone mineral density (BMD) in haemophiliacs with or without co-infections. Methods: 78 adult patients with severe or moderate haemophilia A or B and HIV and/or HCV infection were studied. BMD was measured by dual energy X-ray absorptiometry (DeXA) at femoral area (F) and lumbar spine (L) and was correlated to laboratory values and haemophilic arthropathy assessed using the World Federation of Haemophilia orthopaedic joint scale (WFH score) and the radiological Pettersson score. Results: DeXA showed a homogeneous F-BMD reduction of a part from the belonging group, while L-BMD was significantly lower in pts with HIV and HCV infection (p<0.05). The WFH score was higher in pts with HIV and HCV infection (p<0.002) and in pts with HCV infection (p<0.006). The radiological score was higher in pts with HCV infection than in the other pts (p<0.001). Overall 25-hydroxyvitamin D was reduced in 87% of patients, in particular in 100% of pts with HIV and HCV, 73% of pts with HCV infection and 88% of un-infected subjects. Bone-specific alkaline phosphatase (b-ALP) and telopeptide were increased in all pts (p<0.001 and p<0.01). Conclusions: The worse clinical and radiological scores in patients with infections are most likely related to the amount of patients with more severe coagulopathy in those groups. A high prevalence of hypovitaminosis D has been found in haemophiliacs, a part from the belonging group. The homogeneous F-BMD reduction could be explained by the pivotal role of arthropathy; the lower L-BMD in co-infected and the increase of b-ALP and telopeptide in co-infected and mono-infected groups suggest the faster bone metabolism in case of infections. Disclosure of Interest: None Declared